THE RELATIONSHIP BETWEEN LEARNING ATTITUDE, INTEREST IN LEARNING, MOTIVATION TO LEARN, AND SELF-EFFICACY WITH LEARNING ACHIEVEMENT OF PAI STUDY PROGRAMME STUDENTS IN THE FACULTY OF TARBIYAH AND TEACHER SCIENCE, UIN RADEN FATAH PALEMBANG - Mardeli; Sukirman (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this research is to know the psicologist factor PAI 2015 students. The approach that is used on this research is descriptive quantitative. The subjects of this research are 308 students from class of 2015. Questionnaire is used to collecting the data. The instrument that is used by the researcher is psicologist factor (attitude, Interest, motivation, learning style, self efficacy, and learing achievement). The Descriptive statistic is the techinique that is used in this research. The results are the around 40,90 %, students get highest score in learning attitude, around 47, 08%, students get the high score in learning interest, around 43.50%, students get the lowest score in learning motivation, around 37,34%, students get the highest score in self efficacy, around 49,67%, students get the lowest score in learning style, and around 94,16%, students get medium score in learning achievement. The probability result on spss can be seen in the value of asymp sig (2 tailed) for every variable (attitude, self efficacy, interest, motivation, learnig style and achievement) with the value 0,05. It means the data not normally distributed. From the variable above, only attitude variable that has normal distribution, while the others variable not normally distributed. The other probability result is used multiple correlation analysis on spss. It can be seen on Sig. F change value. The result is less than 0,05, it is 0,017. It means that there is significant correlation between attitude, interest, motivation, efficacy, and learning style gether with students achievement. The purpose of multiple correlation analysis is to identify the degree of closeness in every variable, to identify type of 2 variables relationship and to identify what those relationships are significant.